Customer Value Mediates the Implications of E-Service Quality and E-Payment on Customer Satisfaction for KFCku App Users. - Simanjuntak, Tika M (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: This research aims to analyze the influence of e-service quality and e-payment on customer satisfaction which is mediated by KFCku customer value. The sample used in this research was 185 respondents.Methodology: This type of research uses survey research methods with a quantitative approach. The method used by PLS-SEM is a statistical process that evaluates the outer and inner models (measurement model evaluation and structural model evaluation).Findings: Hypothesis testing proves that H1 (E-service quality on customer value) is accepted; H2 (E-payment to customer value) is accepted; H3 (customer value of customer satisfaction) is accepted; H4 (E-service quality on customer satisfaction) is accepted; H5 (E-payment on customer satisfaction) is accepted; H6 (customer value mediates the relationship between E-service and customer satisfaction) is accepted; and H7 (customer value mediates the relationship between E-payment and customer satisfaction) is accepted.Conclusion: E-service quality and E-payment has a positive and significant effect on the value of customers who use the KFCku application services. Customer Value and E-service quality has a positive and significant effect on customer satisfaction who use the KFCku application services. E-payment has a positive and significant effect on customer satisfaction who use the KFCku application service. Using e-payment in the KFCku application service provides many benefits and convenience for customers. E-service quality, mediated by customer value, has a positive and significant effect on customer satisfaction who use the KFCku application services. E-payment which is mediated by customer value has a positive and significant effect on customer satisfaction who use the KFCku application services.